QUALIFICATIONS AND BASIC COMPETENCIES ANALYSIS OF JAVANESE NEWS ANCHORS IN THE YOGYAWARTA PROGRAM AT TVRI YOGYAKARTA STATION - Eryneta Nurul Hasanah; Tasya Ayu Oktayana (Universitas Sebelas Maret, 2023)
Yogyawarta is a daily news broadcast that covers events in the Yogyakarta region and its surroundings. Yogyawarta is presented by a news anchor wearing traditional Yogyakarta attire and is delivered in the Javanese language, specifically with the highest politeness level (ragam krama inggil), as a representation of the local culture. Naturally, the Yogyawarta news anchor must possess qualifications and basic skills as a good news presenter. This research aims to describe the analysis of the qualifications and basic skills of Javanese-speaking news anchors in Yogyawarta at TVRI Yogyakarta station. The research method used is qualitative-descriptive. The data source for the research consists of Yogyawarta news broadcast videos from the first week of April 2022. Data collection techniques involve observation and documentation. Data analysis is conducted through data reduction, data presentation, and drawing conclusions. The results of this research show that the Yogyawarta news anchors have met 11 qualifications for news anchors, including high intellect, strong personality, proficiency in news reading, credibility, journalistic knowledge and skills, clarity and clarity of voice, understanding and mastery of the medium, concern for listeners, attention to pronunciation, readiness for corrections, and preparedness for emergencies. Yogyawarta news anchors also possess two basic news anchor skills, which include vocal skills and personal skills. The dedication and professionalism of the presenters are demonstrated through their individual styles and abilities, supported by the use of traditional Javanese attire from Yogyakarta.